Funkcija astrocitov - Kržan, Mojca (Zdravniški vestnik, 2001)
Background. Although astrocytes represent 50 of cells in the central nervous system they were recognized as passive, supportive cells regulating homeostasis and creating the microenvironment suitable for neuronal cells to function. Butlately, it was proven that astrocytes possess a unique feature - they are capable of changing their morphology and function throughout life in response to changes in brain microenvironment. Conclusions. They have important functions during development, adulthood and after the brain injury, when they actively participate in the regeneration process or form a scar after excessive neuron loss. Recently discovered functions of astrocytes are: equal partnership in tripartite synapse and active regulation of generation and maintenance of synapses in central nervous system.
Keywords: Age factors; Astrociti; Astrocytes; Brain injuries; Central nervous system diseases; Centralno živčevje, bolezni; Gestacijska starost; Gestational age; Gliosis; Glioza; Možgani, poškodbe; Nerve growth factors; osrednje živčevje; Starostni faktorji; živčevje; živčne celice; Živec, rastni faktorji